The Bible and the Crisis of Modernism : Catholic Criticism in the Twentieth Century. - Petráček, Tomás (University of Notre Dame Press, 2022)
A detailed study of the Catholic Church's acceptance of the historical-critical method and modernization through the pivotal work of European theologians and biblical scholars. One of the few topics in Catholic studies that demonstrates a marked about-face in theological attitudes within the Catholic Church is the reception of the historical-critical method in biblical exegesis and its dramatic rise from outright condemnation in the late nineteenth and early twentieth centuries to its official acceptance by the 1990s. The Bible and the Crisis of Modernism tells the dramatic story of the ultimate acceptance of this modern method by the Catholic Church as it worked out the relationship between faith and reason in view of advances in the social and natural sciences. Particular attention to the contributions of Czech theologians to the field of biblical exegesis foregrounds the tensions at play in the church's gradual recognition of the value of the historical-critical method to a better understanding of the Christian scriptures. In this extensive study of the church's response to the historical-critical method, Petráček broaches wider topics, such as the relationship between the Catholic Church and society in the late nineteenth and twentieth centuries, the modernization of the church in the face of a changing world, the balance between institutional authority and individual freedom of conscience, and the balance between scholarly independence and ecclesial convictions. The attitude of the Catholic Church to modern scholarly research in many ways reflects its complicated relationship to the modern world in general, as The Bible and the Crisis of Modernism shows. Scholars in biblical studies, Catholic studies, and the history of the church in the Czech Republic will find Petráček's work an enlightening addition to their collections.
Description based upon print version of record.
Keywords: Catholic Church -- Doctrines.; Bible -- Criticism, interpretation, etc. -- History.; Église catholique -- Doctrines.; Bible -- Critique, interprétation, etc. -- Histoire.; Catholic Church; Bible; Modernism (Christian theology) -- Catholic Church.; RELIGION / Christian Theology / History; Modernism (Christian theology) -- Catholic Church; Theology, Doctrinal; Criticism, interpretation, etc.; History